Effect of social marketing on the knowledge, attitude, and uptake of pap smear among women residing in an urban slum in Lagos, Nigeria - Tope Olubodun; Mobolanle Rasheedat Balogun; Kofoworola Abimbola Odeyemi; Akin Osibogun; Oluwakemi Ololade Odukoya; Adekunbiola Aina Banjo; Sandra Esse Sonusi; Ayodeji Bamidele Olubodun; Oluwatoyin Olanrewaju Progress Ogundele; Duro Clement Dolapo (BMC, 2022)
Abstract Introduction Nigeria has a low uptake of cervical cancer screening and is one of the five countries that represent over half of the global burden of deaths from cervical cancer. Social marketing principles can be used to design and implement interventions to increase uptake of cervical cancer screening. This study assessed the effect of a social marketing intervention on the knowledge, attitude, and uptake of pap smear among women residing in an urban slum in Lagos State, Nigeria. Materials and methods This was a quasi-experimental study. The intervention arm consisted of 140 women recruited from Ago-Egun Bariga community and the control arm consisted of 175 women recruited from Oto-Ilogbo extension community. Social marketing intervention was instituted in the intervention group. Data analysis was done using IBM SPSS Statistics version 20 and Stata version 16.0. Between groups comparisons and within groups comparisons were done using bivariate analysis with Chisquare, Students t test and Paired t test as appropriate. Results In both the intervention and control groups, the mean knowledge score of cervical cancer was low at baseline (0.0 ± 0.3 and 0.1 ± 0.9 respectively). In the intervention group, there was a significant increase in mean knowledge score to 15.1 ± 3.7, post-intervention (p < 0.001). In both groups, the mean attitude score of cervical cancer was low at baseline (27.1 ± 0.8 in the intervention group and 27.2 ± 1.4 in the control group). In the intervention group, there was a significant increase in mean attitude score to 36.5 ± 4.8, post-intervention (p < 0.001). In both the intervention and control groups, uptake of pap smear was low at baseline (0.0% and 0.6%, respectively). In the intervention group, there was a significant increase in uptake of pap smear to 84.3%, post-intervention (p < 0.001). There was no statistically significant change in knowledge, attitude or uptake of pap smear in the control group, post-intervention. Conclusion This study demonstrated that social marketing intervention can be successful in improving knowledge, attitude, and also the uptake of pap smear, even in settings where these are abysmally low. It is recommended that social marketing intervention be employed as a strategy for improving cervical cancer screening among women residing in slums.